2013
DOI: 10.1242/jeb.082834
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet sensitivity and colour vision in raptor foraging

Abstract: SUMMARY Raptors have excellent vision, yet it is unclear how they use colour information. It has been suggested that raptors use ultraviolet (UV) reflections from vole urine to find good hunting grounds. In contrast, UV plumage colours in songbirds such as blue tits are assumed to be ‘hidden’ communication signals, inconspicuous to raptors. This ambiguity results from a lack of knowledge about raptor ocular media transmittance, which sets the limit for UV sensitivity. We measured ocular media tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 41 publications
1
56
1
Order By: Relevance
“…In our study, differences in light environment had relatively small but non-negligible effects on the mean dichromatism scores and ranks in Galliformes. The JNDs of some of the patches changed by more than 25%, differences considerably larger than those modelled by Lind et al [22]. Our largest observed differences included the daylight 65 (D65) illuminant for both UVS and VS eye types (Table 4).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In our study, differences in light environment had relatively small but non-negligible effects on the mean dichromatism scores and ranks in Galliformes. The JNDs of some of the patches changed by more than 25%, differences considerably larger than those modelled by Lind et al [22]. Our largest observed differences included the daylight 65 (D65) illuminant for both UVS and VS eye types (Table 4).…”
Section: Discussionmentioning
confidence: 50%
“…The importance of this parameter was further demonstrated in behavioral trials which showed that the absence of UV wavelengths reduced the foraging efficiency of three-spined sticklebacks ( Gasterosteus aculeatus Linnaeus; [43]). In contrast, the light environment has almost no effect on the discriminability of vole urine against the vegetation background (~4% JNDs) suggesting little influence on the behavior of foraging raptors [22]. The results from these studies, and others (e.g., [41, 42, 81]), indicate that the importance of the light environment in visual models is context dependent.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations